Makna konseptual dalam metafora pada puisi ‘penguasa dan burung pipit’ karya nizar qabbani : kajian semantik dan stilistika - Zahro, Tazkiyatuz (Maliki Interdisciplinary Journal, 2025)
This study aims to reveal the conceptual meaning within the metaphors found in the poem The Ruler and the Sparrow by Nizar Qabbani through a semantic and stylistic approach. The method used is descriptive qualitative, with data collection techniques involving careful reading and detailed note-taking of metaphorical lines in the poem. The analysis was conducted by classifying the types of metaphors based on the theory of Lakoff and Johnson, followed by interpreting the conceptual meaning of each identified metaphor. The results show that the majority of metaphors in the poem fall under the ontological category, with only one classified as structural metaphor. The conceptual meanings embedded in the lines reflect the poet’s experience of oppression, alienation, and criticism of a repressive sociopolitical context. Symbols such as “sparrow,” “tears,” and “broken glass” represent freedom of thought, emotional suffering, and rejection. These findings reinforce the idea that metaphors are not merely aesthetic devices, but convey deep meanings that reflect human reality and experience in a conceptual framework.